Characteristics of resistance and virulence factors in different species of coagulase-negative staphylococci isolated from milk of healthy sheep and animals with subclinical mastitis - Martins, Katheryne B. [UNESP]; Faccioli, Patricia Y. [UNESP]; Bonesso, Mariana F. [UNESP]; Fernandes, Simone [UNESP]; Oliveira, Aline A. [UNESP]; Dantas, Ariane [UNESP]; Zafalon, Luiz F.; Cunha, Maria de Lourdes R.S. [UNESP] (American Dairy Science Association, 2017)
Coagulase-negative staphylococci (CNS) are among the main responsible agents for mastitis in sheep. Cure rates can be reduced due to several causes, such as those related to virulence factors presented by microorganisms. This study aims at characterizing the virulence and resistance factors to antimicrobial agents in different CNS species isolated from sheep milk. After collecting milk samples, the samples were analyzed and the CNS species were identified. After identification, the susceptibility-sensitivity profile was examined using the disk diffusion technique for 10 antimicrobial agents. The DNA was extracted to detect the presence of the mecA gene, biofilm (icaADBC, bap, and bhp) and toxin genes (sea, seb, sec, sed, tst, and luk-PV) by PCR. Samples carrying toxin genes had their expression assessed using the reverse-transcription PCR technique. The biofilm production was assessed using the adherence method on a polystyrene plate. One hundred twelve CNS samples were isolated, 53 (47.3%) from animals with subclinical mastitis and 59 (52.7%) from healthy animals. Drugs tested have shown to be efficient for most CNS samples. The largest resistance percentage of CNS was found for the penicillin (17.0%) and tetracycline (10.7%) and 4 samples carried the mecA gene. As for the biofilm genes, the icaADBC operon was found in 10 (8.9%) samples, the bap gene was found in 16 (14.3%), and the bhp gene was found in 3 (2.7%). In addition, 69 (61.6%) samples produced biofilm. The survey of toxin genes has shown that 70 (62.5%) samples showed some toxin-encoding gene. However, none of the samples has expressed any of the genes from those toxins studied.
Keywords: biofilm; coagulase-negative staphylococci; resistance; sheep mastitis; toxin